KEDUDUKAN HUKUM CCTV SEBAGAI ALAT BUKTI ELEKTRONIK SETELAH TERBITNYA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 20/PUU-XIV/2016 TANGGAL 07 SEPTEMBER 2016 - Takasya Angela Tanauw Khristanto (Fakultas Hukum Universitas Kristen Indonesia, 2020)
KUHAP as the basis of the implementing Criminal Code Procedure in Indonesia governs that there are 5 valid evidence tools, namely: witness testimony, expert testimony, letters, instructions and information of the defendant. But in its development there are other evidence that is considered legitimate known as electronic evidence tool. CCTV (Closed Circuit Television) is a form of electronic evidence tool that is considered valid according to the law, but after the issuance of Constitutional Court ruling No. 20/PUU-XIV/2016 dated September 07, 2016 which